An in vivo stable isotope-based approach for assessment of absorbed amino acids from individual feed ingredients within complete diets - Estes, K A; White, R R; Yoder, P S; Pilonero, T; Schramm, H; Lapierre, H; Hanigan, M D (Journal of dairy science, 2018)
Accurate assessment of the nutritional content of feed ingredients is required for precise diet formulation. Characterizing ingredients in terms of absorption and digestibility of individual AA is challenging, and this information often relies on indirect methods. The purpose of this research was to evaluate an in vivo stable isotope-based method of determining plasma entry rates of individual AA from feather meal (FM), blood meal (BM), and a rumen-protected AA (RPMet). Abomasal infusions of unprotected Ile, Leu, Met, and sodium caseinate were used as control treatments to assess technique reliability and accuracy. Isotopic enrichment of plasma AA in response to a 2-h constant jugular infusion of a mixture of C labeled AA was measured and modeled using a dynamic 4-pool model, which was fitted to each AA by infusion to derive diet entry rates. The resulting entry rate matrix was used to derive plasma entry rates of individual AA from each ingredient by regression. The mean of plasma AA entry for abomasally infused Ile, Leu, and Met was 93.4 ± 7.35% of that infused, indicating that 6.6% was used by splanchnic tissues during first pass. The mean of the plasma essential AA entry for abomasally infused casein was 86.7 ± 4.81% of that present in the source protein, which represents a mean of 8.7% first-pass use assuming 95% digestibility. Individual AA appearances ranged from 86 to 93% of the source content except Ile, which was 73%. These fractional appearance percentages were similar to those previously reported when using a dietary regression approach. The mean plasma essential AA entry rate for FM was 52.7% of the AA in the source ingredient, with a range across AA of 48 to 58%. The mean plasma essential AA entry rate for BM was 47.5%, with a range of 30 to 61%. However, estimated Met availability from the RPMet was lower (9.9%) than expected (42%). This may be due to the relatively larger errors of measurement for Met entry rates and a small change in RPMet inclusion. Assuming that rumen-undegraded protein absorption is reflective of aggregated essential AA entry rates after correction for first-pass use, 52.6 and 61.2% of dietary FM and BM CP was absorbed from the intestine, respectively, which yielded an estimated intestinal digestibility of 70 and 66%, respectively. This method appears to provide an accurate and precise in vivo assessment of individual AA plasma entry rates that can be used to better characterize individual feed ingredients in ruminants. Such information will result in more robust economic assessments of feeds and increased precision of diet formulation.